2015
DOI: 10.1111/desc.12346
|View full text |Cite
|
Sign up to set email alerts
|

Facial speech gestures: the relation between visual speech processing, phonological awareness, and developmental dyslexia in 10‐year‐olds

Abstract: Successful communication in everyday life crucially involves the processing of auditory and visual components of speech. Viewing our interlocutor and processing visual components of speech facilitates speech processing by triggering auditory processing. Auditory phoneme processing, analyzed by event-related brain potentials (ERP), has been shown to be associated with impairments in reading and spelling (i.e. developmental dyslexia), but visual aspects of phoneme processing have not been investigated in individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 91 publications
0
7
0
1
Order By: Relevance
“…A passive audio–visual oddball paradigm was constructed from the syllables /pa/ and /ga/, because the phonemes /p/ and /g/ distinguish between different word meanings in German (e.g., /platt/− flat vs. /glatt/– slippery ) and have been shown to be discriminable both auditorily and visually ( Schaadt et al 2015 , 2016 , 2019 ). Children were presented with a video of a frequently occurring standard mouth movement while hearing either the congruently produced syllable or a mismatching syllable.…”
Section: Methodsmentioning
confidence: 99%
“…A passive audio–visual oddball paradigm was constructed from the syllables /pa/ and /ga/, because the phonemes /p/ and /g/ distinguish between different word meanings in German (e.g., /platt/− flat vs. /glatt/– slippery ) and have been shown to be discriminable both auditorily and visually ( Schaadt et al 2015 , 2016 , 2019 ). Children were presented with a video of a frequently occurring standard mouth movement while hearing either the congruently produced syllable or a mismatching syllable.…”
Section: Methodsmentioning
confidence: 99%
“…One is the number of participants. Although the sample size is similar, or even larger, than in previous comparable research on facial speech processing in dyslexia (e.g., Rüsseler et al, 2018;Schaadt et al, 2016), it is fully possible that with even greater number of participants, and increased statistical power, more subtle differences between groups would be statistically apparent. That would also allow for a more robust exploration of mediating and moderating effects such as those of age, gender, general cognitive ability, and comorbidity with other neurodevelopmental or psychopathological conditions.…”
Section: Discussionmentioning
confidence: 96%
“…804). Similarly, Schaadt et al ( 2016 ) presented dyslexic and non-dyslexic 10-year-olds with a video recording of a speaker’s mouth that was silently pronouncing syllables. They found that non-dyslexic children displayed an increased posterior response to a sudden change in the “pronounced” syllable (known as the visual mismatch response (vMMR)) consistent with processing of visual input.…”
Section: Introductionmentioning
confidence: 99%
“…Electrode impedances were kept below 5 kΩ in most cases (at least below 10 kΩ). We digitized the electrical signals with a sampling rate of 500 Hz (Schaadt, Männel, van der Meer, Pannekamp, & Friederici, 2015). …”
Section: Methodsmentioning
confidence: 99%